Some phytochemical and morphophysiological characteristics of Euphorbia cyparissias L. populations - Papp, Nóra; Szabó, László Gy. (Acta Biologica Szegediensis, 2002)
Perennial plants are able to adapt to different ecological habitats with their morphological and physiological characteristics. In this study some population of cyparissias L. were investigated. This stress tolerant species can adapt to its environment with morphological and reproductive marks. Differences were not detected in the presence of the investigated phytochemical compounds, only in their respective quantity, considering the extracts from Stem, leaf and inflorescence.